Direct Gaze Partially Overcomes Hemispatial Neglect and Captures Spatial Attention - Leal Rato, Miguel; Mares, Inês; Aguiar de Sousa, Diana; Senju, Atsushi; Martins, Isabel Pavão (Frontiers in Psychology, 2019)
Direct gaze has been shown to be a particularly important social cue, being preferentially processed even when unconsciously perceived. Results from several visual search tasks further suggest that direct gaze modulates attention, showing a faster orientation to faces perceived as looking toward us. The present study aimed to analyze putative modulation of spatial attention by eye gaze direction in patients with unilateral neglect. Eight right hemisphere stroke patients with neglect performed a target cancellation paradigm. Patients were instructed to cross all open-eyed pictures amidst closed eyed distractors. Target images were either in direct or averted gaze. Participants performed significantly better when observing targets with direct gaze supporting the hypothesis that this gaze direction captures attention. These findings further suggest that perception of direct gaze is able to diminish the visuospatial impairment seen in neglect patients.